Stiff person case misdiagnosed as conversion disorder: A case report - Saeed Razmeh; Amirhasan Habibi; Farzad Sina; Elham Alizadeh; Monireh Eslami (Babol University of Medical Sciences, 2017)
Background: Stiff person syndrome (SPS) is a rare neurological disease resulting in stiffness and spasm of muscles. It initially affects the axial muscles and then spread to limb muscles. Emotional stress exacerbated the symptoms and signs of the disease. The pathophysiology of the disease is caused by the decreased level of the glutamic acid decarboxylase (GAD) activity due to an autoantibody against GAD that decreases the level of gamma-aminobutyric acid (GABA). In this paper, we present a case of atypical presentation of SPS with lower limb stiffness misdiagnosed as conversion disorder. Case presentation: We report a patient with atypical presentation of SPS with lower limb stiffness and gait disorder misdiagnosed as conversion disorder for a year. Her antithyroid peroxidase antibody (anti-TPO Ab) level was 75 IU (normal value: 0–34 IU). Intravenous immunoglobulin (IVIG) was administered (2gr/kg, 5 days) for the patient that showed significant improvement in the follow-up visit. Conclusion: It is essential that in any patient with bizarre gait disorder and suspicious to conversion disorder due to the reversibility of symptoms, SPS and other movement disorder should be considered.